Six ways to get a grip on teaching medical trainees on the convergence of Indigenous knowledges and biomedicine, within a culturally-safe Indigenous health curriculum - Sayal, Aarti; Richardson, Lisa; Crawford, Allison (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
As Indigenous knowledges and biomedicine come together in healthcare today, to improve health outcomes and strengthen cultural identity among Indigenous Peoples, it is vital for physicians to learn about this convergence during their training. This narrative review article aims to provide practical advice for educators when implementing teaching regarding this topic, using examples from the research literature, and pedagogical and practice-based methods used at the University of Toronto (UofT). The methodology on obtaining the research literature included a search of a computer database called Medline. Moreover, the medical school curriculum information specific to UofT, was obtained through the formal curriculum map and UofT’s Office of Indigenous Medical Education. The following six recommendations provide a way to successfully implement the teachings on Indigenous knowledges and biomedicine, within a culturally-safe Indigenous health curriculum.